2017
DOI: 10.9746/jcmsi.10.149
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of the Rise to Stand Movements Using Bereitschaftspotential from Scalp Electroencephalography (EEG)

Abstract: : The negative-going Bereitschaftspotential (BP) is associated with the preparation and execution of dynamic movement. So far, BP for simple movements involving either the upper or the lower body has been studied. However, BP has not yet been recorded during both movements. Our study reveals that the negative-going BP was evoked around 3 to 2 seconds before the onset of the rise in response to a start cue. The BP had a negative peak before the onset of the movement of the trunk. BP for the rise to standing up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have shown the effects of task complexity on ERD/ERS rhythms and the complexity of the sit-to-stand and stand-to-sit movements (Bulea et al, 2014;Singh et al, 2017;Mashat et al, 2019;Chaisaen et al, 2020). To overcome these limitations, we used information from the idle state, a neutral condition, to facilitate the classifier's recognition of distinctive characteristics of the related motor imagery task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the effects of task complexity on ERD/ERS rhythms and the complexity of the sit-to-stand and stand-to-sit movements (Bulea et al, 2014;Singh et al, 2017;Mashat et al, 2019;Chaisaen et al, 2020). To overcome these limitations, we used information from the idle state, a neutral condition, to facilitate the classifier's recognition of distinctive characteristics of the related motor imagery task.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have only been tested in offline scenarios due to the complexity of the movements and experimental setups that produce unrealistic EEG signals when compared to experimental setups in online scenarios (Rodríguez-Ugarte et al, 2017). Only a small number of studies have been conducted on standing and sitting behaviors in offline scenarios (Zhou et al, 2007;Bulea et al, 2014;Singh et al, 2017;Chaisaen et al, 2020). Therefore, we examined the use of an EEG-based BCI to decode offline and online MI information for these types of movements.…”
Section: Introductionmentioning
confidence: 99%
“…3. These electrodes were selected for signal processing because of their low electrode impedance and their relationship with the sensorimotor areas that are most significant for discrimination between different ME and MI tasks, such as imaginary/physical standing up movement (Bulea, Prasad, Kilicarslan, & Contreras-Vidal, 2014;B. Singh, Wagatsuma, & Natsume, 2017).…”
Section: Preprocessingmentioning
confidence: 99%